Selection and Warning of Evidence-Based Antidiabetic Medications for Patients With Chronic Liver Disease - Yen, Fu-Shun; Hsu, Chih-Cheng; Wei, James Cheng-Chung; Hou, Ming-Chih; Hwu, Chii-Min (Frontiers in Medicine, 2022)
The global prevalence of chronic liver disease and diabetes mellitus (DM) has gradually increased probably due to changes in diet and lifestyle. The choice of antidiabetic medications for patients with coexisting DM and chronic liver disease is complicated. Severe liver injury may decrease the metabolism of antidiabetic medications, resulting in elevated drug concentrations and adverse effects. The choice of antidiabetic medications in patients with chronic liver disease has not been well studied. The long-term outcomes of antidiabetic medications in patients with chronic liver disease have gained attention recently. Herein, we reviewed relevant articles to extend our understanding on the selection and warning of antidiabetic medications for patients with chronic liver disease.